(untitled) (INTERNATIONAL SCIENTIFIC-ELECTRONIC JOURNAL “PIONEERING STUDIES AND THEORIES”, 2025)
Point defects in semiconductors—such as vacancies, interstitials, and antisite defects—significantly influence the photovoltaic properties of these materials, affecting the efficiency of devices like solar panels. These defects alter the semiconductor’s electronic structure, impacting the absorption of sunlight and the generation of electron-hole pairs crucial for electricity production. While some defects act as recombination centers, reducing efficiency by causing premature electron-hole recombination, others can be engineered to enhance material properties through techniques like doping. This paper explores the dual nature of point defects, both as impediments and as potential enhancers of photovoltaic efficiency. We discuss how advanced material processing techniques, including thermal annealing, ion implantation, and laser doping, are utilized to control defect formation and improve the photovoltaic response of semiconductors. Additionally, we highlight ongoing research aimed at better understanding and controlling these defects, leveraging high-resolution imaging and computational modeling. This research is pivotal for optimizing the design and enhancing the performance of photovoltaic devices, thereby advancing the development of sustainable energy technologies.